Pengaruh Keterampilan, Stres Kerja, Dan Lingkungan Terhadap Produktivitas Kerja Karyawan Muslim Pt. Daiwabo Garment Indonesia Pemalang - Dyah Muhayaroh; Rinda Asytuti (Journal of Islamic Economics and Finance, 2022)
Employee productivity is important for the company, if productivity is high, the sustainability of the company will be guaranteed and vice versa. Work productivity can be influenced by various factors such as skills, job stress, and work environment. This research aims to determine how much influence the skills, work stress, and work environment have on the work productivity of the employees of PT. Daiwabo Garment Indonesia Pemalang. This study uses multiple linear regression analysis. The population in this study were employees of PT. Daiwabo Garment Indonesia, which is in factory one, totaling 673 employees. The sampling technique used was simple random sampling and determining the number of samples using the Slovin formula in order to obtain a total of 88 respondents. The collection method used a questionnaire. The results showed that partially the variables of skills, work stress, and work environment had a significant effect on the work productivity of the employees of PT. Daiwabo Garment Indonesia Pemalang. Simultaneously the variables of skills, work stress, and work environment have a significant effect on the work productivity of the employees of PT. Daiwabo Garment Indonesia Pemalang.